Sub-picosecond passively mode-locked thulium-doped fiber laser by ReS2 nanoparticles. (29th December 2020) - Zhou, Yong; Fang, Changji; Zhang, Zhengxiong; Tong, Liang; Ma, Xiaohui; Zhang, Wei; Yu, Ronghua; Gao, Weiqing; Xu, Jun; Liao, Meisong; Suzuki, Takenobu; Ohishi, Yasutake
Abstract: Passively mode-locked pulses generated in a thulium-doped fiber laser was demonstrated by the ReS2 nanoparticles. The ReS2 nanoparticles are introduced into the laser cavity on a side polished fiber through optical deposition method, which works as a saturable absorber. Self-starting mode-locking can be established quickly when the pump power is higher than 700 mW. The central wavelength and the 3 dB bandwidth of single pulse operation are 1970.65 and 5.05 nm, respectively. The pulse repetition is 26.1 MHz and the full width at half maximum is 893 fs with the time-bandwidth product of 0.348.